2013
DOI: 10.1179/2046905512y.0000000023
|View full text |Cite
|
Sign up to set email alerts
|

Lingual frenulum and effect on breastfeeding in Thai newborn infants

Abstract: Tongue-tie is not uncommon and is associated with breastfeeding difficulty in newborn infants. Mothers of infants with severe tongue-tie should be closely and individually coached during breastfeeding and followed up, especially during the first critical weeks of the infant's life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0
10

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 14 publications
1
33
0
10
Order By: Relevance
“…The knowledge and skills of health care professionals regarding EBF were also been reported to have a positive impact on EBF rates [18]. Moreover, supportive health care services, including a 6 month post-natal check, 24 hour counselling, hotlines, home visits, telephone follow up, nurse support, breastfeeding guidelines, education programmes, breastfeeding promotion programmes and good access to healthcare in the antenatal and postpartum periods were reported as facilitators of EBF [45,50,61,68,73,74,[81][82][83]87,[93][94][95][96][97][98][99][100][101][102][103][104][105][106][107][108][109][110][111][112].…”
Section: Healthcare Professional and Health Care System Factormentioning
confidence: 99%
“…The knowledge and skills of health care professionals regarding EBF were also been reported to have a positive impact on EBF rates [18]. Moreover, supportive health care services, including a 6 month post-natal check, 24 hour counselling, hotlines, home visits, telephone follow up, nurse support, breastfeeding guidelines, education programmes, breastfeeding promotion programmes and good access to healthcare in the antenatal and postpartum periods were reported as facilitators of EBF [45,50,61,68,73,74,[81][82][83]87,[93][94][95][96][97][98][99][100][101][102][103][104][105][106][107][108][109][110][111][112].…”
Section: Healthcare Professional and Health Care System Factormentioning
confidence: 99%
“…Not all breastfed infants with TT will have breast-feeding difficulties. Messner et al reported an incidence of 25% and Ngerncham et al reported incidences of 11.8% and 37.9% in moderate and severe tongue ties respectively [2,3]. It is important to note that Ngerncham et al clearly illustrated the multifactorial nature of breastfeeding problems identifying maternal nipple length/inversion and sensation of the infant's tongue on the nipple as independent risk factors for problems [3].…”
Section: Effect On Breastfeedingmentioning
confidence: 91%
“…Messner et al reported an incidence of 25% and Ngerncham et al reported incidences of 11.8% and 37.9% in moderate and severe tongue ties respectively [2,3]. It is important to note that Ngerncham et al clearly illustrated the multifactorial nature of breastfeeding problems identifying maternal nipple length/inversion and sensation of the infant's tongue on the nipple as independent risk factors for problems [3]. O'Callahan et al demonstrated that breastfeeding difficulties can occur irrespective of whether the tongue tie is anterior or posterior, although they did note a preponderance in posterior tongue ties amongst the patient group referred [13].…”
Section: Effect On Breastfeedingmentioning
confidence: 99%
See 1 more Smart Citation
“…Such features may restrict tongue movements to varying degrees. Ankyloglossia can be classified as mild or partial, which is the most common type, and severe or complete, a rare condition in which the tongue is fused to the floor of the oral cavity (5) . Thus, in severe cases, this membrane interferes with the free movement of the tongue and the alteration in the lingual frenulum implies consequences in the functions of suction and speech.…”
Section: Introductionmentioning
confidence: 99%